PENERAPAN WAKAF UANG SECARA PROFESIONAL MENURUT HUKUM ISLAM (Application of Cash Waqf in Good Governance) - Ahmad Mu’is; Binti Nur Hamida (Qawanin: Jurnal of Economic Syaria Law, 2020)
In term of terminology, the word Waqf means 'holding back something to acquire advantage'. Certain things can be something active like land or passive like money as cash waqf (waqf al nuqud). Money as waqf is still not explored and managed to the maximum, even though its potential is massive because Indonesia is a majority Muslim country. The great potential of waqf challenges is also not easy. The main obstacle is more on human resources and their management strategies. The problem of good and efficient management of waqf is a problem. Therefore, the greater the wealth and diversity of waqf that can be managed by Nadzhir professionally with proper management, the more benefits can be derived from managing cash waqf with good governance will strengthen the role of waqf in improving the economy and welfare of the community. This research uses literature study method by referring several primary and secondary sources in the form of books, and relevant journals discussing the problems of waqf, money waqf, and good governance. The results of this study state that in the context of waqf management, Good Governance can be more easily interpreted as trustful waqf management so that waqf property can be collected, managed and distributed properly for the benefit of the people. Potential money as cash waqf is also very promising, because waqf in this form are not with ownership of large amounts of wealth. Key words: Waqf, Cash Waqf, Good Governance